Educação de adultos com deficiência intelectual grave: entre a exclusão social e o acesso aos direitos de cidadania - Noronha, Lucélia Fagundes Fernandes (2014)
This study aims to investigate the social and educational practices brought to effect by a specialized institution providing social-educational services to seriously handicapped individuals, to the extent that apparent cognitive loss is recognized in such individuals and the need for social and educational practices targeting their development. The data have made it apparent that despite segregated they cannot be regarded as socially excluded. They are offered a service regarded as of high-life-quality standard seeking to develop educational practices which, once recognizing these limitations, seek to broaden their personal autonomy, thus allowing their access to human rights and citizenship. Data collecting has been performed through the institution s organizing documents, the proposals, reports, and social and educational activity evaluations. Qualitative treatment to the data was based upon theoretical contributions, regarding citizenship and education rights, by Martuccelli, Cury, and Bittar; social exclusion and inclusion, Martins theoretical perspectives; and development and learning, in Vygotsky s conceptions